Patterns of multidrug resistance in Salmonella isolated from commercial layers during 4 months of rearing in Mymensingh, Bangladesh (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: Antibiotic-resistant bacterial pathogens from livestock and poultry pose a significant global concern, contributing to many foodborne and zoonotic diseases. This study aimed to detect Salmonella spp. from selected poultry farms during a defined study period, with a particular focus on antibiotic resistance. Materials and Methods: One hundred and five cloacal swabs were obtained aseptically from birds of seven randomly selected commercial layer farms of Mymensingh district in Bangladesh. The isolation of Salmonella spp. was performed through culturing on selective agar media and subsequently confirmed by polymerase chain reaction (PCR) using specific primers. The disc diffusion method was performed to determine the sensitivity of confirmed Salmonella spp. isolates against 19 antibiotics. Finally, PCR was performed to detect the tetracycline (tetA) and beta-lactamase (blaTEM) genes. Results: Out of 105 samples, 34 were detected as positive for Salmonella spp. on Salmonella-Shigella media, of which 20 (19.05%) isolates were confirmed as Salmonella spp. (211 bp). Erythromycin, cefuroxime, doxycycline, amoxicillin, ampicillin, and tetA were ineffective against all 20 isolates. Several unique antibiotic resistance patterns were observed, with most isolates exhibiting multidrug resistance (MDR). Furthermore, 100% of the phenotypically resistant isolates contained the tetA and blaTEM genes. Conclusion: Commercial layers in Bangladesh were found to harbor MDR Salmonella spp., representing a potential risk to the poultry population and a public health concern.J. Adv. Vet. Anim. Res., 12(4): 1142–1150, December 2025http://doi.org/10.5455/javar.2025.l975